Morphological description and Histological structure of the liver in Passer domesticus (House sparrow) - Entikhab H. Abed; Nahla A. AL-Bakri (Journal of Madenat Alelem University College, 2011)
This study showed that liver of Passer domesticus bilobed the right lobe is cardiac shape while the left is elliptical and the liver colour is brown. It is occupying most of anterior and middle parts of abdominal cavity. The liver is surrounded by Glison capsule which is represented by a thin layer of connective tissue with septum extend peripherally in liver tissue. The liver tissue is formed from polyhedral hepatocyte arrange as irregular hepatic cord surrounded the central vein. Each cell contains one or two nucleus with one or more nucleolus. The blood sinusoid appeared between the liver cells .The hepatic cord arranged radially around the central vein. The portal area is clear and surrounded by connective tissue. Gallbladder is almost pear shaped with dark green colour and situated between the liver lobes. Histologically, it consists of three layers (Mucosa which formed from columnar epithelium based on lamina propria, muscular layer of circular arrangement smooth muscle and the third layer is the externa which represented by thin layer of loose connective tissue).